2016
DOI: 10.5750/ejpch.v4i1.1056
|View full text |Cite
|
Sign up to set email alerts
|

Consultant Pharmacist Case Management of Older People in Intermediate Care: a New Innovative Model

Abstract: Rationale, Aims and Objectives: In 2011, ‘Transforming Your Care’ outlined the remodelling of Health and Social Care in Northern Ireland (HSCNI) UK, specifically recommending better integration of hospital and community services for older people. This work aimed to evaluate consultant pharmacist case management for older patients admitted from acute to intermediate care continuing back into the community setting, given the importance of such a transition to person-centered healthcare.  Method: On transfer to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…This is similar to the 53% reported in Eadon's original (hospital-based) study, but lower than the 84% reported during an analysis of the effect of consultant pharmacist case management of older people in intermediate care. 15,17 This lower value is perhaps expected as, community pharmacists are unlikely to possess the resources (in terms of specialist knowledge, multidisciplinary team support, time for repeated follow-up and ability to conduct home visits) afforded to a consultant pharmacist in care of the elderly. Assigning a monetary value to these interventions appears to show a four-fold return on investment, even when using the most conservative estimate of value delivered per dMUR conducted.…”
Section: Intervention Type Scorementioning
confidence: 99%
“…This is similar to the 53% reported in Eadon's original (hospital-based) study, but lower than the 84% reported during an analysis of the effect of consultant pharmacist case management of older people in intermediate care. 15,17 This lower value is perhaps expected as, community pharmacists are unlikely to possess the resources (in terms of specialist knowledge, multidisciplinary team support, time for repeated follow-up and ability to conduct home visits) afforded to a consultant pharmacist in care of the elderly. Assigning a monetary value to these interventions appears to show a four-fold return on investment, even when using the most conservative estimate of value delivered per dMUR conducted.…”
Section: Intervention Type Scorementioning
confidence: 99%
“…The model was developed in 2009 and is, therefore, likely to underestimate the current healthcare costs, and it is unclear if this model is applicable to the PEOLC population. However, its use is established within pharmacy services in Northern Ireland and was warranted in the absence of a suitable alternative, with mitigation measures employed to compensate [24][25][26]. Despite these limitations, economic analysis of the interventions demonstrates that not only does the palliative care pharmacist influence the appropriateness and safety of medicine use in this patient population, there is also likely to be an associated cost saving.…”
Section: Discussionmentioning
confidence: 99%
“…This model refers to all medicine-related costs. The model was established to evaluate other pharmacist-led services in Northern Ireland and is linked to the Eadon intervention ranking scale [25,26]. Each Eadon-graded intervention can be assigned an associated cost avoidance as illustrated in Table 2.…”
Section: Cost Avoidancementioning
confidence: 99%
“…More than 10 years ago, the Royal Pharmaceutical Society of Great Britain outlined how pharmacists could contribute to IC services [28]. Whilst there remains a lack of involvement from the community pharmacy sector of the profession, there have been emerging examples of innovative models of clinical pharmacist-led care pathways under development in England [29] and NI [30]. This study suggests that the most pertinent barrier to CP involvement is the existing workload that CPs currently face.…”
Section: Discussionmentioning
confidence: 99%